2006
DOI: 10.1111/j.1471-0528.2006.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

General gynaecology: Association of phthalate esters with endometriosis in Indian women

Abstract: Sample Blood samples were collected from 49 infertile women with endometriosis (study group); 38 age-matched women without endometriosis (control group I) but with infertility related to tubal defects, fibroids, polycystic ovaries, idiopathic infertility and pelvic inflammatory diseases diagnosed by laparoscopy and a further group of 21 age-matched women (control group II) with proven fertility and no evidence of endometriosis and other gynaecological disorders during laparoscopic sterilisation.Methods Concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
102
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(113 citation statements)
references
References 50 publications
6
102
3
2
Order By: Relevance
“…The findings of the present study confirmed the results of the previous reports (6)(7)(8) showing the higher DEHP levels in women with endometriosis. Furthermore, the present study revealed that the increase of the plasma level of monoethylhexyl phthalate, the main metabolite of DEHP, was more pronounced than DEHP in patients with advanced-stage endometriosis, which seems to be a novel finding.…”
supporting
confidence: 96%
See 1 more Smart Citation
“…The findings of the present study confirmed the results of the previous reports (6)(7)(8) showing the higher DEHP levels in women with endometriosis. Furthermore, the present study revealed that the increase of the plasma level of monoethylhexyl phthalate, the main metabolite of DEHP, was more pronounced than DEHP in patients with advanced-stage endometriosis, which seems to be a novel finding.…”
supporting
confidence: 96%
“…Cobellis et al (6) reported for the first time that the plasma concentration of DEHP is elevated in women with endometriosis compared with the controls in an Italian population. Reddy et al (7,8) also showed an increased plasma level of DEHP in an Indian population, along with increased levels of other phthalate esters and polychlorinated biphenyls. However, recent studies have revealed contradictory findings by measuring urinary phthalate metabolite concentrations, warranting a further investigation in prospective studies (9,10).…”
mentioning
confidence: 89%
“…During these years their presences in the environment in large quantities have been confirmed, but the results of different studies about their toxicity and persistence concluded that phthalates were not dangerous for human health. However, during the last few years, their activity as endocrine disruptors, their impact on the normal development of living organisms, as well as their teratogenic activity in both human and animal studies have caused them to be considered new emerging contaminants [2,3]. As a result, a high amount of research is now being conducted in order to know their levels and behavior in the environment and in humans, their main pollution sources as well as the way to decrease their levels around us [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…One of the key acts is weight) suggest that exposure to levels higher than ambient ones is necessary to induce relevant changes (44). Although increased DEHP, DBP, BBP, and di-n-octyl phthalate (DOP) levels were detected in the blood of women with endometriosis (45,46), the problems in immune system functioning could also trigger the development of endometriosis (35).…”
Section: Phthalate Migration and Regulationsmentioning
confidence: 99%